Effect of Initial Backfill Temperature on the Deformation Behavior of Early Age Cemented Paste Backfill That Contains Sodium Silicate - Aixiang Wu; Yong Wang; Bo Zhou; Jiahua Shen (Advances in Materials Science and Engineering)
Enhancing the knowledge on the deformation behavior of cemented paste backfill (CPB) in terms of stress-strain relations and modulus of elasticity is significant for economic and safety reasons. In this paper, the effect of the initial backfill temperature on the CPB’s stress-strain behavior and modulus of elasticity is investigated. Results show that the stress-strain relationship and the modulus of elasticity behavior of CPB are significantly affected by the curing time and initial temperature of CPB. Additionally, the relationship between the modulus of elasticity and unconfined compressive strength (UCS) and the degree of hydration was evaluated and discussed. The increase of UCS and hydration degree leads to an increase in the modulus of elasticity, which is not significantly affected by the initial temperature.